Reliable classification of facial phenotypic variation in craniofacial microsomia: a comparison of physical exam and photographs - Birgfeld, Craig B. (Head Face Med, 2016)
BACKGROUND: Craniofacial microsomia is a common congenital condition for which children receive longitudinal, multidisciplinary team care. However, little is known about the etiology of craniofacial microsomia and few outcome studies have been published. In order to facilitate large, multicenter studies in craniofacial microsomia, we assessed the reliability of phenotypic classification based on photographs by comparison with direct physical examination. METHODS: Thirty-nine children with craniofacial microsomia underwent a physical examination and photographs according to a standardized protocol. Three clinicians completed ratings during the physical examination and, at least a month later, using respective photographs for each participant. We used descriptive statistics for participant characteristics and intraclass correlation coefficients (ICCs) to assess reliability. RESULTS: The agreement between ratings on photographs and physical exam was greater than 80 % for all 15 categories included in the analysis. The ICC estimates were higher than 0.6 for most features. Features with the highest ICC included: presence of epibulbar dermoids, ear abnormalities, and colobomas (ICC 0.85, 0.81, and 0.80, respectively). Orbital size, presence of pits, tongue abnormalities, and strabismus had the lowest ICC, values (0.17 or less). There was not a strong tendency for either type of rating, physical exam or photograph, to be more likely to designate a feature as abnormal. The agreement between photographs and physical exam regarding the presence of a prior surgery was greater than 90 % for most features. CONCLUSIONS: Our results suggest that categorization of facial phenotype in children with CFM based on photographs is reliable relative to physical examination for most facial features.